CHARACTERIZATION OF REFERENCE ELECTRODE AG/AGCL DRY TYPE BY CYCLIC VOLTAMMETRY - -, Herawatil; -, B. Buchari; -, I. Noviandri (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
In the present work the characterisazion of reference electrode Ag/AgCl type dry by 0.01 M [Fe(CN) in 0.1 M KCl using the technique of cyclic voltammetry  at potential range of -0.2 to 0.8 V and scan rate variation..The anodic (Epa) and the cathodic (Epc) peak potentials. as well as the corresponding anodic (ipa) and cathodic(ipc) peak currents. were obtained at different scan rates (10. 20. 25. 50. 100. and 200)  mV/s . The half-wavepotentials (E1/2) of the [Fe(CN)6]4-/ [Fe(CN)6]3- couple in the investigated solvent media have been evaluated. Ipversus v1/2 have been calculated using the Randles-Sevcik equation..Keywords: cyclic voltammetry. half-wave potential. reference electrode Ag/AgCl6]3-/4-